A multi-laboratory study of diverse RSV neutralization assays indicates feasibility for harmonization with an international standard. Issue 23 (25th May 2017) - Hosken, Nancy; Plikaytis, Brian; Trujillo, Carrie; Mahmood, Kutub; Higgins, Deborah; ,
Highlights: A wide variety of RSV neutralization assay formats are currently used by the field. This study assessed the current level of agreement between twelve assay formats. Results showed precision was consistently high, whereas agreement varied widely. Results indicated harmonization could be improved with an international standard. Results provided information on samples that may be appropriate for IS development. Abstract: A current barrier to the standardized evaluation of respiratory syncytial virus (RSV) vaccine candidates is the wide variety of virus neutralization assay formats currently in use for assessing immunogenicity. Assay formats vary widely in labor intensiveness, duration, and sample throughput. Furthermore, the cell lines and virus strains used are not consistent among formats. The purpose of this multi-laboratory study was to assess the variability across a diverse array of assay formats that quantitate RSV neutralizing antibodies. Using a common specimen panel, the degree of overall agreement among existing assays was evaluated to inform on the need for harmonization of assay results. A total of 12 laboratories participated in the blinded survey study by testing a panel comprised of 57 samples chosen to span the reportable titer range of the assays. An independent statistical analysis was conducted to measure overall agreement of assay results. This analysis showed that precision was consistently high, whereas agreement varied widely among assays. To examine whether agreement could be improved, we conducted a harmonization exercise using a variety of sample types as pseudo standards. The results showed that the level of agreement could be improved, and provided information on the suitability of samples for developing an international standard.